Prevalence of musculoskeletal discomfort (msd) among heeled shoe user: the correlation between the foot regions and discomfort - Nor ‘Amirah binti Talib; Ismaniza binti Ismail; Surniza binti Mohd Hilmin (Southeast Asian Journal of Technology and Science, 2020)
The purpose of this study is to analysis the correlation between the foot regions and discomfort among heeled shoes user. This study used the quantitave correlation method with 250 sample. The questionnaire was adapted from the standardized Nordic questionnaire and Cornell Musculoskeletal Discomfort questionnaire. Result shows that there is relationship between heel height and the discomfort at foot palm. The cumulative percentage of discomfort at forefoot area 2 (F2) have the highest percentage (20.4 %) followed by hindfoot (19.58 %), forefoot area 5 (F5) and midfoot (18.06 %), Forefoot area 1 (F1) (14.3 %) and Forefoot area 4 (9.5 %). Based of the result it is recommended to have more education exposure related to MSD prevalence as most of the wear do not aware the risk of foot discomfort may lead to low back pain if ignoring the foot discomfort. Further research is needed in order to find the most suitable height of the heel shoes in minimizing the risk of having foot MSD.